Investigation on nanoscale material removal process of BK7 and fused silica glass during chemical‐mechanical polishing. (10th January 2021) - Wang, Lin; Zhou, Ping; Yan, Ying; Guo, Dongming
Abstract: Understanding the nanoscale material removal process in chemical mechanical polishing (CMP) is of fundamental importance for the operation and further development of CMP. In this study, the nanoscale material removal processes of both fused silica glass and BK7 glass were investigated based on single‐pad‐asperity polishing experiments. The results indicate that the material removal characteristics are highly dependent on the composition and structure of glass materials. In the mechanically induced chemical bonding removal mode, only atoms locate near the outermost several layers can participate in the formation and breakage of interfacial bridge bonds. Moreover, the force on the abrasive particle must exceed a threshold value to induce significant removal of Si atoms from the glass substrate, because as the breakage of Siglass –O backbonds does not occur in low‐stress conditions. We reveal for the first time that the chemical and mechanical properties of the topmost layer, which is recognized as densification, hydrated, or redeposition layer, have not been significantly affected by the mechanical action of the abrasive particles when polishing in this kind of material removal mode. The results are expected to provide a deeper insight into the nanoscale material removal mechanism during glass CMP.